Pioneer Rocketry MRL Wisconsin Space Conference Proceedings - Lee, Brian (Proceedings of the Wisconsin Space Conference, 2023)
The Minnesota Space Grant Consortium hosts the Midwest High-Power Rocket Competition every year. This year the competition involved designing and constructing a diverse fleet of three, five, or eight rockets. This fleet of rockets was to be diverse in construction techniques, shape, and size while following a theme. Each competition team was also tasked with constructing a standardized “core” kit rocket that counted toward the total number of rockets for the fleet. Points were awarded for the design, flight, and accuracy of the simulation of each rocket. Pioneer Rocketry constructed eight unique rockets under the theme of mythical creatures. Since all three team members had previously obtained an L1 High Powered Rocketry Certification, the team constructed three L2 Certification rockets. The construction of a diverse armada of eight rockets presented the team with many challenges that granted the team learning experiences. On launch day, the team only successfully launched three rockets due to personnel and time constraints.